PERENCANAAN JARINGAN KOMUNIKASI HALTE TRANSJAKARTA KORIDOR 13 DENGAN TEKNOLOGI GIGABIT PASSIVE OPTICAL NETWORK (GPON) - Sutrisno, Agus; Purnawan, Peby Wahyu (MAESTRO, 2020)
The need for public transportation services is needed for metropolitan cities like Jakarta. Public transportation can support faster mobility. To support the service requirements required communication networks and have good media access. In this thesis will discuss the design of the Transjakarta communication network from stop to stop in corridor 13 and Helte to BLU Jakarta by using optical fiber media with passive optical Gigabit technology Network that is connected to the Central Transjakarta Network. Corridor 13 has 15 stops starting from Tendean Stop until Ciledug Stop. From the design that is made using FTTH network architecture with the components of the optical fiber transmission network (transmitter), transmission and receiver media (receiver) and provides several devices that can be categorized in active and passive components. In the design of this thesis, discuss the Giga technology standards in accordance with ITU-T G.984. From the laying down of the network infrastructure in question, the total attenuation value of the Ministry of Foreign Affairs has been analyzed until the customer gets the lowest value of 11.5 dB and the highest value of 26.8 dB has met the standard of ​